Digital Marketing of Purbayan Tourism Village Yogyakarta Through Instagram @kamwispurbayan in Facing Competition of Tourism Destinations - Fikrani Deslia, Iva; Ikmalina Faza, Fadhila (Universitas Ahmad Dahlan, 2024)
Purbayan Tourism Village is one of the villages in Kota Gede Yogyakarta, located at Jalan Canteng No.29, RT 37/RW 09, Purbayan, Kota Gede District, Yogyakarta City, Special Region of Yogyakarta. This village used to be an ordinary village, which has a distinctive feature, namely the existence of the remains of the Ancient Mataram Kingdom building and is famous for its silver-making crafts in Kota Gede Yogyakarta; gradually, this village became a tourist village. This study applies the SOSTAC Method in marketing Purbayan Tourism Village. The SOSTAC Method comprises six stages: Situational Analysis, Objective, Strategy, Tactic, Action, and Control. This study aims to understand how applying the SOSTAC Method can help Purbayan Tourism Village improve their marketing effectiveness. The research approach used is literature studies, documentation, and interviews with data analyzed descriptively. The study results show that applying the SOSTAC Method allows Purbayan Tourism Village to identify opportunities in planning and implementing marketing strategies. Suggestions for Purbayan Tourism Village include maximizing the use of social media, not just focusing on one social media. For the most actively used Instagram social media, there needs to be deeper monitoring related to the data collection of the number of views, followers, followers, and the number of visitors to the Instagram account, as well as the content created, so that it becomes an evaluation in conducting digital promotions through Instagram. There needs to be an increase in marketing in the field of social media so that it can maximize by increasingly productive human resources.